The ethics and regulation of cell and tissue therapies in the UK - Lowdell, Mark (Henry Stewart Talks, 2015)
What is an ATMP, Specific regulations covering cell therapies, Academic development process, ATMP stakeholders, Ethical issues, legislation and regulation, ATMP development